Accounting For Non-Current Assets Held For Sale And Discontinued Operations (Eurasian Journal of History, Geography and Economics, 2025)
Today in Uzbekistan there are some issues in the practical application of IFRS. To find a solution to these problems, in this article we want to reveal the essence of IFRS 5 “Noncurrent assets held for sale and discontinued operations” and give some explanations of the organization of accounting for non-current assets held for sale according to international accounting standards and the preparation of financial statements, showing their practical application using the specific examples.